2021
DOI: 10.1021/acs.jafc.0c07281
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Life Stage-Associated Lipidome Remodeling in Atlantic Salmon

Abstract: Salmon is an important source of long-chain highly unsaturated fatty acids (LC-HUFAs) such as 22:6 n -3 [docosahexaenoic acid (DHA)]. In the present study, we conducted two identical experiments on salmon in freshwater (FW) and seawater (SW) stages, with a diet switch from fish oil (high in LC-HUFA) to vegetable oil (low in LC-HUFA) and vice versa. Our aim was to investigate the diet and life stage-specific features of lipid uptake (gut), processing (liver), and deposition (muscle). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Some studies carried out on fish show that the esterification of fatty acids in the sn-1/2 positions varies depending on the species and living conditions, observing that the abundance of phospholipids in the muscle of Salmo salar was lower in fish reared in seawater compared to freshwater fish, except PC and PE 44:12, which were present in greater abundance in the latter group [ 21 ], which is consistent with the results of this study. Additionally, Song et al [ 16 ] determined by REIMS (negative scan mode) that the main n-7 lipid species detected in Salmo salar fillet correspond to phospholipids such as PC 16:1-18:1, PC 16:1-20: 2, PE 16:1-18:1 and PE 16:1-18:0, unlike those of other species, such as tuna, butterfish and shrimp, among other organisms.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies carried out on fish show that the esterification of fatty acids in the sn-1/2 positions varies depending on the species and living conditions, observing that the abundance of phospholipids in the muscle of Salmo salar was lower in fish reared in seawater compared to freshwater fish, except PC and PE 44:12, which were present in greater abundance in the latter group [ 21 ], which is consistent with the results of this study. Additionally, Song et al [ 16 ] determined by REIMS (negative scan mode) that the main n-7 lipid species detected in Salmo salar fillet correspond to phospholipids such as PC 16:1-18:1, PC 16:1-20: 2, PE 16:1-18:1 and PE 16:1-18:0, unlike those of other species, such as tuna, butterfish and shrimp, among other organisms.…”
Section: Resultssupporting
confidence: 91%
“…Likewise, a recent study determined the effect of the inclusion of palm and flaxseed oil in seawater and freshwater conditions in the diet on lipidome remodeling (UPC2-MS/MS, positive-mode scanning) of Salmo salar (200 g in weight) muscle, showing that the main lipids present in this species correspond to triacylglycerols, phosphatidylcholine and phosphatidylethanolamine. It was observed that seawater allows for more active lipidome remodeling than freshwater-reared fish, mainly due to the more active lipid metabolism in the smoltification process [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…On fish so far, few lipidome data are available in relation to crosstalk between organs, maybe due to a key fat storage in liver in some species, or only the existence of white fat adipose tissue, whereas in mammals, brown adipose tissue is involved as well ( 175 , 176 ). To our knowledge, lipidome reports rather appeared in relation to fish environment or diet, focusing more on lipid metabolism than on lipokines ( 177 , 178 ). For instance, Dreier et al.…”
Section: Lipokinesmentioning
confidence: 99%
“…162 The identification of lipid metabolites and the assessment of the variation in their composition have been explored using LC-MS in order to comprehend lipid metabolic changes occurring in fish as a response to factors that break the homeostasis of an organism, such as alterations in temperature, diet and life-stages. 157,165 The lipidome analysis of skeletal muscle from obscure pufferfish (Takifugu fasciatus) demonstrated that PL metabolites increased under cold stress through activation of the MAPK pathway. 157 A comparative study using Atlantic salmon in freshwater and seawater life-stages showed a different dynamic remodelling of the lipid class composition of gut, liver and muscle tissues when fish trailed a change in its diet (fish oil vs. vegetable oil).…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
“…157 A comparative study using Atlantic salmon in freshwater and seawater life-stages showed a different dynamic remodelling of the lipid class composition of gut, liver and muscle tissues when fish trailed a change in its diet (fish oil vs. vegetable oil). 165 DI-MS approaches also provided significant information to elucidate the effects of diet and genetic background on TG and PL metabolism in Atlantic salmon muscle tissue. 160,161 Marine mammals have recently been the subject of some lipidomic studies, which were focused on the cetacean family (whales, dolphins and porpoises).…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%